Adsorptive separation of butanol, acetone and ethanol in zeolite imidazolate frameworks with desirable pore apertures. (2nd February 2022) - Wang, Jing; Wu, Jinglan; Zheng, Bin; Wang, Jiang; Shi, Qi; Dong, Jinxiang
Graphical abstract: Highlights: The adsorbent window parameters represent a control dimension on the affinity to ABE. MAF-6 with larger aperture is promising adsorbents to separate butanol from ABE. ZIF-71 with medium aperture is promising adsorbents to separate acetone/ethanol. ZIF-11 with smaller aperture is promising adsorbents to adsorb ethanol. Abstract: The objective of this work was to study the separation of fermentation-derived acetone–butanol–ethanol (ABE). Three hydrophobic zeolite imidazolate frameworks (ZIFs) with representative pore apertures were screened to investigate the structure–property relationships. The results show that increasing the pore aperture of ZIFs leads to a substantial decrease in the adsorption amounts and affinity for acetone and ethanol because ZIFs having larger apertures possess weaker interactions with more polar acetone and short-chain ethanol. Butanol adsorption on MAF-6 with a larger aperture (7.4 Å) is 247.7 mg g −1 and the selectivities of butanol/acetone and butanol/ethanol are 15.6 and 8.4, respectively, which exceeds that of traditional adsorbents. In addition, ZIF-71 with medium aperture and ZIF-11 with smaller aperture are promising adsorbents to separate acetone/ethanol and adsorb ethanol, respectively. Thus, the concept of adsorbent pore aperture parameters that represent a control dimension on the affinity toward the target ABE component is proposed.